2021
DOI: 10.1021/acsearthspacechem.0c00332
|View full text |Cite
|
Sign up to set email alerts
|

Large Discrepancy in the Formation of Secondary Organic Aerosols from Structurally Similar Monoterpenes

Abstract: The two monoterpenes, Δ3-carene and α-pinene, have very similar chemical structures, which leads to the assumption that the formation of secondary organic aerosol (SOA) is also similar. This study aims to investigate if the formation of SOA from ozonolysis of Δ3-carene and α-pinene is actually analogous. This is addressed by conducting smog chamber studies of Δ3-carene ozonolysis and comparing the results to similar studies of α-pinene. Detailed offline analysis using ultra-high-performance liquid chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(81 citation statements)
references
References 67 publications
(146 reference statements)
8
73
0
Order By: Relevance
“…Hyttinen et al: Vapor pressures of α-pinene + O 3 products Monoterpenes (C 10 H 16 ) are an abundant class of BVOCs emitted by various plants (Guenther et al, 1995). The oxidation mechanisms of monoterpene reactants vary significantly, leading to products with different SOA formation capabilities (Thomsen et al, 2021). Additionally, the initial oxidant (i.e., OH, O 3 and NO 3 ) affects the SOA formation rates of the oxidation products (Kurtén et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyttinen et al: Vapor pressures of α-pinene + O 3 products Monoterpenes (C 10 H 16 ) are an abundant class of BVOCs emitted by various plants (Guenther et al, 1995). The oxidation mechanisms of monoterpene reactants vary significantly, leading to products with different SOA formation capabilities (Thomsen et al, 2021). Additionally, the initial oxidant (i.e., OH, O 3 and NO 3 ) affects the SOA formation rates of the oxidation products (Kurtén et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, αpinene, a very abundant monoterpene in the atmosphere, has been widely studied in both laboratory and field experiments (Docherty et al, 2005;Hall and Johnston, 2011;Hao et al, 2011;Ehn et al, 2012Ehn et al, , 2014Kristensen et al, 2014;Lopez-Hilfiker et al, 2015;McVay et al, 2016;D'Ambro et al, 2018;Huang et al, 2018;Claflin et al, 2018;Ye et al, 2019), and α-pinene oxidation, with both O 3 and OH, is efficient at producing oxygenated organic molecules and SOA. Consequently, the oxidation mechanism and potential structures of α-pinene + O 3 products have been extensively studied both experimentally and computationally Berndt et al, 2018;Kurtén et al, 2015;Iyer et al, 2021;Lignell et al, 2013;Aljawhary et al, 2016;Mutzel et al, 2016;Kristensen et al, 2020;Thomsen et al, 2021). Various methods have been used for estimating the saturation vapor pressures or saturation mass concentrations of α-pinene ozonolysis products (Ehn et al, 2014;Kurtén et al, 2016;D'Ambro et al, 2018;Buchholz et al, 2019;Peräkylä et al, 2020;Räty et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Thomsen et al (2021) identified multiple carboxylic acids in SOA formed in α-pinene ozonolysis experiments using an ultra-high performance liquid chromatograph (UHPLC). Out of the compounds included in Thomsen et al (2021) (Bilde and Pandis, 2001;Lienhard et al, 2015;Babar et al, 2020) are given for the specific isomer, while COSMOtherm15 values (Kurtén et al, 2016) are for various other isomers. Babar et al (2020) and Kostenidou et al (2018), respectively.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Monoterpenes (C 10 H 16 ) are an abundant class of BVOCs emitted by various plants (Guenther et al, 1995). The oxidation mechanism of monoterpene reactants vary significantly, leading to products with different SOA formation capabilities (Thomsen et al, 2021). Additionally, the initial oxidant (i.e., OH, O 3 and NO 3 ) affects the SOA formation rates of the oxidation products (Kurtén et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation